Spatiotemporal variation in irrigation water requirement and drought assessment for major crops in Shanxi Province - WANG Wei; CUI Qingliang; QIANG Shengcai; ZHANG Yan (Guan'gai paishui xuebao)
【Objective】 Agriculture is the largest water consumer in Shanxi Province. Understanding the water requirements of major crops is important for improving water resource management and the development of sustainable agriculture in the province. This paper studies the spatiotemporal variations in irrigation water requirements and drought assessment for major crops in the province. 【Method】 The reference evapotranspiration (ET0) was calculated using the Penman-Monteith formula based on daily meteorological data from 1960 to 2019 at 28 weather stations across the province. Using the single crop coefficient method, we calculated the water requirements (ETc) and irrigation requirements (IR) of spring maize, summer maize, spring wheat, winter wheat, cotton and potato. The spatial distributions of effective precipitation, temperature, ET0, ETc and IR for each crop were analyzed using ArcGIS to evaluate drought frequency and its impacts across the province. 【Result】 Spatially, ET0 and average daily temperature vary consistently across the province, decreasing from South to North up to Wutai and Youyu, then increasing further northward. Temporally, except for potato, the IR of other crops has been decreasing from 1960 to 2019, with their IR varying spatially. The average IR of major crops over the 1960—2019 period ranked as follows: winter wheat (293.23 mm) > spring wheat (144.74 mm) > spring maize (142.81 mm) > cotton (131.89 mm) > summer maize (82.81 mm) > potato (74.56 mm). During growing periods of crops, the influence of droughts, when occurring, were regional. 【Conclusion】 Precipitation can basically meet the demands of summer maize, spring maize and spring wheat need for irrigation during their rapid growth periods. However, winter wheat, cotton, and potato require irrigation during their mid-growth periods.